LAYANAN PERPUSTAKAAN PERGURUAN TINGGI DI MASA AWAL PANDEMI COVID-19: STUDI KASUS UNIVERSITAS GADJAH MADA - Kadek Aryana Dwi Putra; Fauzan Hidayatullah (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This study aims to see how the UGM library responded at the beginning of the COVID-19 pandemic. This paper describes the state of the library at Gadjah Mada University since it was closed in early March 2020 until November 2020. In addition, this paper provides details on how libraries have adapted during the COVID-19 pandemic. The research method used is descriptive qualitative. Data were collected from web pages, blogs, social media and interviews. The results show that the Gadjah Mada University library has undergone a service transformation that implements the COVID-19 health protocol. Almost all library services are virtualized. Therefore, there are several challenges faced by librarians and users in carrying out virtual activities in the library.